PENERAPAN METODE TAGUCHI UNTUK PERBAIKAN KUALITAS PENGEMASAN TEPUNG TAPIOKA DI PT. FLORINDO MAKMUR - Khoiri, M Miftahul; Harahap, Uun Novalia; Zaharuddin, Zaharuddin (Universitas Putera Batam, 2024)
Improving the quality of a product is the most essential thing for a company to continue to exist in the business world and as an important factor affecting the level of development and progress of the company. This research was conducted to identify the causes of defects in tapioca flour packaging at PT. Florindo is prosperous so that it can reduce the amount of damage and provide suggestions for improvements to the tapioca flour packaging containing 500 grams. The data used are primary data and secondary data by conducting experiments using the taguchi method. The dependent variable used is the improvement in the quality of tapioca flour weighing 500 grams with the independent variables namely the lack of workers (HR), speed of filling flour and temperature heater. The results showed that the speed of filling flour as a factor that significantly influences the quality of tapioca flour packaging with a contribution percentage of 67.3% so that the right settings and models for tapioca flour packaging so that quality packaging according to specifications is produced is the human resource factor. 3 workers, the flour filling speed factor is slowed down to 2.7 seconds/pcs and the Temperature Heater factor is 150 ℃.